2018
DOI: 10.1111/eip.12756
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and access to care in first‐episode psychosis

Abstract: Aim: Mental health-related stigma is considered a significant barrier to help-seeking and accessing care in those experiencing mental illness. Long duration of untreated psychosis is associated with poorer outcomes. The impact of stigma on the duration of untreated psychosis, in firstepisode psychosis remains unexplored. To examine the association between mental healthrelated stigma and access to care in people experiencing first-episode psychosis in Birmingham, UK. Methods:We collected data on a prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
1
28
1
Order By: Relevance
“…As would be expected when compared to individuals with multiple episodes of mental illness, this level of perceived stigma is somewhat lower than the average level of stigma in the sample of 193 service users (27% schizophrenia–schizoaffective disorder) reported on for the development of the Stigma Scale , for which the average score for the total Stigma Scale was 2.23 (on a 5‐point scale, ranging 0–4) and for the 6‐item abbreviated scale was 2.43, between the ‘neither agree nor disagree’ (2) and ‘agree’ (3) anchors. The level of perceived stigma in this study also appears slightly higher than that reported in the Kular et al study of 89 persons with FEP, where the average rating on the 5‐point Stigma Scale was 1.7, between the ‘disagree’ (1) and ‘neither agree nor disagree’ (2) anchors. Interestingly, the DUP of participants in the RAISE‐ETP study was somewhat longer (median = 74 weeks) than in the Kular et al study (median = about 52 weeks), which could account for some of the higher rate of perceived stigma in this study.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…As would be expected when compared to individuals with multiple episodes of mental illness, this level of perceived stigma is somewhat lower than the average level of stigma in the sample of 193 service users (27% schizophrenia–schizoaffective disorder) reported on for the development of the Stigma Scale , for which the average score for the total Stigma Scale was 2.23 (on a 5‐point scale, ranging 0–4) and for the 6‐item abbreviated scale was 2.43, between the ‘neither agree nor disagree’ (2) and ‘agree’ (3) anchors. The level of perceived stigma in this study also appears slightly higher than that reported in the Kular et al study of 89 persons with FEP, where the average rating on the 5‐point Stigma Scale was 1.7, between the ‘disagree’ (1) and ‘neither agree nor disagree’ (2) anchors. Interestingly, the DUP of participants in the RAISE‐ETP study was somewhat longer (median = 74 weeks) than in the Kular et al study (median = about 52 weeks), which could account for some of the higher rate of perceived stigma in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent quantitative study by Kular et al did show that perceived stigma (using the full version of the Stigma Scale used in this study) was significantly associated with a longer DUP in a sample of 89 persons beginning treatment for FEP, although data on symptoms were not reported. The present study extends the findings of Kular et al by demonstrating that perceived stigma is predictive of a longer DUP after controlling for symptom severity.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Such delay can be related to several factors. These certainly include reduced access to care due to stigma and self‐stigma surrounding mental illness 25‐27 , but stigma‐derived or data‐based concerns about the safety of psychotropic medications in children and adolescents are also relevant 28‐34 .…”
mentioning
confidence: 99%
“…Patients with higher levels of stigma-related negative feelings will have a higher tendency to avoid receiving treatment. When attitudes of acceptance towards MDD are high, it becomes easier for MDD sufferers to receive medication and psychotherapy (Carrara & Ventura, 2018;Latalova, Kamaradova, & Prasko, 2014;Tucker et al, 2013), especially in the early phase of the disorder (Firmin et al, 2018;Kular et al, 2018); that is, the feelings of stigma affect the outcome of the disorder by affecting the treatment compliance of MDD patients. The possible mechanism underlying this tendency is shown in Figure 1.…”
mentioning
confidence: 99%